Calculated interdiffusivities resulting from different fitting functions applied to measured concentration profiles in Cu-rich fcc Cu-Ni-Sn alloys at 1073 K - Liu Y.; Liu D.; Du Y.; Liu S.; Kuang D.; Deng P.; Zhang J.; Du C.; Zheng Z.; He X. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Employing six groups of bulk diffusion couples together with electron probe microanalysis technique, the compositiondependences of ternary interdiffusion coefficients in Cu-rich fcc Cu-Ni-Sn alloys at 1073 K were determined via the Whittle and Green method. Different fitting functions applied to the measured concentration profiles are utilized to extract the interdiffusion coefficients of fcc Cu-Ni-Sn alloys. The errors for the obtained interdiffusivities are evaluated by a scientific method considering the error propagation. The calculated diffusion coefficients using the Boltzmann and additive Boltzmann functions are found to be with reasonable errors and show a general agreement with those using other fitting functions. Based on the Boltzmann and additive Boltzmann functions, the interdiffusivities in Cu-rich fcc Cu-Ni-Sn alloys at 1073 K are obtained and validated by thermodynamic constraints. The Boltzmann and additive Boltzmann functions are recommended to be used for the fitting of measured concentration profiles in other ternary systems for the sake of extracting ternary diffusivities.